(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2024)
This article explores the linguocreative potential and manifestations of linguistic creativity in Otto Häuser’s satirical "Ottokar" book series. The study defines the concept of linguistic creativity, identifies its characteristic features, and presents the main expressive devices employed in the author’s texts. The theoretical foundations of linguistic creativity are examined alongside grammatical, lexical, and stylistic aspects. Lexical devices appear most frequently in the novels, allowing for their classification into distinct groups. The author’s most commonly used techniques include ironic expressions, comparisons, metaphors, and phraseological modifications. Special attention is given to metaphors and their modification techniques; pictorial comparisons and their functioning in literary texts; occasional word formations and their creative potential; and humor types at both word and sentence levels. The analysis reveals how Häuser masterfully employs wordplay, transformed phraseological units, zeugma, speaking names, and other devices to create a multi-layered humorous narrative that reflects the social and cultural context of GDR Germany.